Supplementary irrigation for sequential cropping in the Ethiopian highland Vertisols using broadbed and furrow land management system - Astatke, A.; Airaksinen, H.; Mohamed-Saleem, M.A. (Elsevier, 1991)
Examines the effects of broadbed and furrow land management systems and supplementary irrigation on the productivity of sequentially planted wheat and chickpea on Vertisols wheat was grown during the main rainy season on boradbeds and furrows made with an animal drawn implement to drain off the excess water. The wheat harvest was followed by planting of chickpea in the begining of the dry season. Through the furrows four irrigation treatments were applied. The results showed that if the rain stops offer planting the second crop, chickpea will not emerge without irrigation. Irrigation at planting gave the highest grain yield while three irrigations, viz, no irrigation; at planting & vegetative stage; at planting, vegetative stage & 50 percent flowering gave lower grain yield.